Iron loading is a prominent feature of activated microglia in Alzheimer’s disease patients - Kenkhuis, Boyd; Somarakis, Antonios; de Haan, Lorraine; Dzyubachyk, Oleh; IJsselsteijn, Marieke E.; de Miranda, Noel F. C. C.; Lelieveldt, Boudewijn P. F.; Dijkstra, Jouke; van Roon-Mom, Willeke M. C.; Höllt, Thomas; van der Weerd, Louise (Acta neuropathologica communications, 2021)
Brain iron accumulation has been found to accelerate disease progression in amyloid-β(Aβ) positive Alzheimer patients, though the mechanism is still unknown. Microglia have been identified as key players in the disease pathogenesis, and are highly reactive cells responding to aberrations such as increased iron levels. Therefore, using histological methods, multispectral immunofluorescence and an automated in-house developed microglia segmentation and analysis pipeline, we studied the occurrence of iron-accumulating microglia and the effect on its activation state in human Alzheimer brains. We identified a subset of microglia with increased expression of the iron storage protein ferritin light chain (FTL), together with increased Iba1 expression, decreased TMEM119 and P2RY12 expression. This activated microglia subset represented iron-accumulating microglia and appeared morphologically dystrophic. Multispectral immunofluorescence allowed for spatial analysis of FTL + Iba1 + -microglia, which were found to be the predominant Aβ-plaque infiltrating microglia. Finally, an increase of FTL + Iba1 + -microglia was seen in patients with high Aβ load and Tau load. These findings suggest iron to be taken up by microglia and to influence the functional phenotype of these cells, especially in conjunction with Aβ.